Los sistemas de reciprocidad migratoria: comprendiendo el sistema de visado argentino - Korstanje, Maximiliano (Nómadas. Critical Journal of Social and Juridical Science, 2008)
At present time, tourism has become a massive activity in a large part of the world. However, the nations still put certain restrictions to regulate the entrance and traffic for because of tourism or labor migration. This article is intended to analyze and deepen in what represents the visa systems, comparing the results with the American anthropologist's reciprocity Marshal Sahlins model.
Keywords: Tourism; Migration; Visa; Reciprocity